Serum resistin positively correlates with serum lipids, but not with insulin resistance, in first-degree relatives of type-2 diabetes patients: an observational study in China. Issue 16 (April 2017) - Niu, Xiao-hong; Li, Li; Li, Jun-yan; Song, Qi; Jin, Miao-miao; Liu, Jin-xia
Abstract : Abstract: To investigate whether serum resistin correlated with hypertension, obesity, dyslipidemia, or insulin resistance (IR) in Chinese type 2 diabetes mellitus (T2DM) patients and their first-degree relatives (DFDRs) in a case–control observational study. We determined the serum levels of resistin, plasma lipids, glucose, and insulin, and performed clinical assessments of hypertension, obesity, and IR for 42 T2DM patients, 74 of their DFDRs, and 51 healthy control participants with no family history of T2DM (NC group). The biochemical and clinical variables were compared between the 3 groups, and relationships between serum resistin and the other variables were evaluated using a Pearson correlation analysis. Significant trends were observed in the triglyceride, HbA1c, and resistin levels, in which the values observed in the DFDR group were intermediate to those of the T2DM and NC groups ( P  < .05 for all). A stratified analysis revealed significant trends in the resistin level and scores for homeostasis model assessment (HOMA) indexes for IR and insulin sensitivity in women and in the HbA1c and resistin levels in men ( P  < .05 for all), with DFDR subjects exhibiting intermediate values. The Pearson analysis showed that serum resistin positively correlated with total cholesterol and low-density lipoprotein cholesterol in the DFDR group only ( P  < .05 for both), and that resistin did not correlate significantly with HOMA indexes, blood glucose, insulin, HbA1c, triglyceride, high-density lipoprotein cholesterol, BMI, waist or hip circumference, or blood pressure. Our results suggest that elevated serum resistin might contribute to an increased risk of hyperlipidemia in DFDRs of Chinese T2DM patients.